French Vocabulary Learning Strategies of French Majors at Khon Kaen University - Kurawan, Wanrudee (Pattimura University, 2022)
The present study sought to investigate learning strategies and French vocabulary memorization strategies as well as to examine French vocabulary learning strategies employed among French-majored students at Khon Kaen University with high, moderate and low levels of GPA. In particular, the participants were 89 French-majored students, including second-year, third-year, and fourth-year students. In data collection, the instruments used in this study were a 38-item questionnaire concerning learning strategies and French vocabulary memorization strategies adapted from Schmitt’s Vocabulary Learning Strategies Questionnaire (2000). Statistics used to analyze the collected data included percentage, mean, and standard deviation. The results demonstrated that the most frequently used strategy for the discovery of a new word’s meaning was determination strategies, the most commonly used of which were using a French-Thai dictionary application and guessing word meaning from textual context respectively. Concerning strategies for consolidating a word, the most frequently employed was memory strategies. Pronouncing the word aloud while studying and practicing its spelling were two of the most frequently used strategies. In the meantime, in terms of cognitive strategies, most often employed were written repetition and the use of an application for taking notes and memorizing words. Lastly, regarding metacognitive strategies, most frequently utilized among the students were learning and memorizing words through social media as in Facebook, Twitter, and Instagram. Comparing strategies employed among the students with high, moderate and low levels of GPA, it was found that the strategy for the discovery of a new word’s meaning most frequently employed among all these groups was using the French-Thai dictionary application. Despite that, the students with a high GPA tended to employ more various vocabulary memorization strategies than those with a moderate and low GPA did. It was also discovered that all three groups rarely